-TOCOPHEROL IMPROVED THE QUALITY OF BEAGLE DOG BREED CHILLED SEMEN STORAGE AT 4 C IN TRIS-SKIM MILK EXTENDER - Makhroja, Lalu Faris Naufal; Juniantito, Vetnizah; Fahrudin, Mokhamad; Prasetyaningtyas, Wahono Esthi; Karja, Ni Wayan Kurniani (Jurnal Kedokteran Hewan, 2025)
Improvement of canine reproduction has been developed by artificial insemination (AI) for effective breeding. -tocopherol widely recognized as an antioxidant that has been used to improve the quality of the spermatozoa. This study evaluated the effect of -tocopherol supplementation in dog chilled semen quality. Beagle dog breed semen samples were obtained from male Beagles using massage technique. The semen was then diluted with tris-skim milk extender supplemented with -tocopherol of various concentration, 0% as control group (T-0), 0.1% (T-0.1), 0.2% (T-0.2), and 0.3% (T-0.3), then were stored at 4 C and evaluated daily for four days, particularly for variables namely sperm motility, sperm viability, and plasma membrane integrity. Results showed that the quality of spermatozoa was higher when spermatozoa preserved in extender containing of 0.1% or 0.2% -tocopherol compared to those of control and 0.3% -tocopherol group (P0.05). The highest quality found in group with 0.2% -tocopherol. In conclusion, supplementation -tocopherol 0.2% in dog chilled semen extender is effective for improving and maintaining chilled dog sperm quality for 4 days of storage.